Introduction to food engineering. - Singh, R.Paul, ....-; Heldman, Dennis R., ....- (Amsterdam : Elsevier, 2009)
The fourth edition of this leading textbook presents the engineering concepts and unit operations used in food processing in a classroom-proven and unique blend of principles with applications. Describing the application of a particular principle followed by the quantitative relationships that define the related processes, each chapter also includes solved examples and problems to evaluate reader comprehension.